2009
DOI: 10.1002/jpln.200800014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenate addition on selenium accumulation and plant growth of two Prunus rootstock genotypes

Abstract: A pot experiment was conducted with two Prunus genotypes (GF 677 and Mr.S.2/5, commercial rootstocks for peach), which are widely used in Italy and other European countries. Selenium (Se) was added as sodium selenate to 3‐month‐old micropropagated plants at a rate of 0 (control), 1.0, 2.5, and 5.0 mg Se (kg soil)–1. Plant growth, gas exchange, and Se accumulation were studied. Selenium added at a rate of 2.5 and 5.0 mg Se kg–1 appeared to be highly toxic for the two young peach rootstocks. Thirty‐three days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…This result indicates that the Se (VI) treatment may affect the degree of stomatal opening of rice leaves. It has been reported that Se (VI) can reduce the value of stomatal conductance to induce a partial stomatal closure in two Prunus rootstock genotypes (Pezzarossa et al, 2009), which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that the Se (VI) treatment may affect the degree of stomatal opening of rice leaves. It has been reported that Se (VI) can reduce the value of stomatal conductance to induce a partial stomatal closure in two Prunus rootstock genotypes (Pezzarossa et al, 2009), which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Decrease in plant growth and yield with increased DTPA and EDDS application were also reported some research (Turan and Angin 2004;Turan and Esringu 2007;Wu et al 2007;Angin et al 2008;Pezzarossa et al 2009). …”
Section: Discussionsupporting
confidence: 53%
“…However, those studies mostly selected inorganic Se (Na 2 SeO 3 and Na 2 SeO 4 ) as the main form of Se fertilizer. With inorganic Se dual effects on plants, the excessive Se addition inhibited plant growth, resulting in reduced plant growth and a high mortality rate . Thus inorganic Se fertilizer is not suitable for Se fertilizer application.…”
Section: Discussionmentioning
confidence: 99%
“…With inorganic Se dual effects on plants, the excessive Se addition inhibited plant growth, resulting in reduced plant growth and a high mortality rate. 34 Thus inorganic Se fertilizer is not suitable for Se fertilizer application. This study concluded that spraying a 500× dilution of amino acid-chelated Se-enriched foliar fertilizer, which plants absorbed easily and with no harm to plants or humans, has contributed to increasing the Se content of grape berries.…”
Section: Discussionmentioning
confidence: 99%